Discusiones en torno a la presunción de la inocencia en el ámbito jurídico angloamericano - Díaz, Ernesto Matías (2024)
This paper systematizes and compares, based on the reasoning of the U.S. Supreme Court and its decisions, four pairings of concepts that arise from discussions on the operability of the presumption of innocence in the Anglo-American legal system. The article illustrates that the partial conclusions in each of these comparisons must be reached by arguments consistent with the normative foundation of the presumption of innocence principle in order to find the defining characteristics of said principle. Ultimately, the paper sets forth a definition of the presumption of innocence that encompasses each of the partial conclusions thus reached.